2014
DOI: 10.3189/2014aog66a031
|View full text |Cite
|
Sign up to set email alerts
|

Topographic and geometric controls on glacier changes in the central Tien Shan, China, since the Little Ice Age

Abstract: (2) relative area changes of glaciers are strongly affected by two of these local factors (glacier area and mean elevation); and (3) ELA change does not show a strong relationship with local factors, suggesting that it may be controlled mainly by climatic factors. This study provides important insights into the local controls on glacier changes at the centennial timescale, which are of critical importance to assess future glacier changes in this arid and semi-arid region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 42 publications
(65 reference statements)
2
30
1
Order By: Relevance
“…In contrast to reports from many other regions of the globe (e.g. Li and Li, 2014;Fischer et al, 2015;Paul and Mölg, 2014), glacier aspect showed no statistical correlation with any of the glacier change parameters, which may result from the summertime midnight sun over Svalbard and the more balanced insolation on slopes with northern and southern aspects, compared to midlatitudes. Pearson correlation coefficients of glacier change parameters against other parameters and glacier geometry variables are given in Table 3.…”
Section: Links Between Glacier Change Indicators and Their Geometrycontrasting
confidence: 99%
“…In contrast to reports from many other regions of the globe (e.g. Li and Li, 2014;Fischer et al, 2015;Paul and Mölg, 2014), glacier aspect showed no statistical correlation with any of the glacier change parameters, which may result from the summertime midnight sun over Svalbard and the more balanced insolation on slopes with northern and southern aspects, compared to midlatitudes. Pearson correlation coefficients of glacier change parameters against other parameters and glacier geometry variables are given in Table 3.…”
Section: Links Between Glacier Change Indicators and Their Geometrycontrasting
confidence: 99%
“…). Li and Li () analysed 487 modern glaciers and their corresponding LIA glacial advances in the central Tian Shan, and found that the relative area of shrinkage of glaciers are affected strongly by glacier size: small glaciers tend to undergo greater change due to their relatively smaller area of accumulation. The areas of modern glaciers in the TK and SR valleys are about 2.1 and 7.6 km 2 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Palaeo‐ELAs were estimated using the Toe to Summit Altitude method (TSAM) (Benn and Lehmkuhl, ; Li and Li, ). This method averages the elevation of the glacier terminus and highest elevation within the glacier valley to obtain the ELA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results show that topographical glacier parameters exercise great controls on mutual variations and, thus, the response of the glacier to the similar climatic environment [14].There are important studies in the literature examining these effects (elevation, slope, aspect, etc.) that cause heterogeneity on glacier retreat [14,20,[32][33][34]. The previous study especially focused on the topographical analysis of glacier retreat and glaciation on Mount Agri [34].…”
mentioning
confidence: 99%